Altered hearing function in mice with implanted cranial windows - Jovanović, Nataša; Suchánková, Štěpánka; Kang, Minseok; Melichar, Adolf; Bureš, Zbyněk; Tureček, Rostislav (Neuroscience letters, 2023)
The cranial window technique has proven to be an effective method for in vivo imaging of cortical activity. However, given the invasive nature of this procedure, possible side effects could be expected in the nervous system. In this study, we evaluated the effects of unilateral cranial window surgery on auditory function in C57BL6 mice using electrophysiological and behavioral approaches. We found that one week after implantation, mice exhibited both increased thresholds and decreased amplitudes of their auditory brainstem responses. These changes were accompanied by a decrease in distortion product otoacoustic emissions, indicating a deterioration in cochlear function. In addition, behavioral testing of these mice revealed reduced suppression of their acoustic startle response by gap prepulse, suggesting a deficit in auditory processing or possibly the presence of tinnitus. The changes in auditory function appeared to be only partially reversible within four weeks after surgery. Thus, our findings suggest that cranial window implantation causes long-term functional changes in the auditory system that should be considered when interpreting data from optical imaging techniques.
Keywords: myši inbrední C57BL; sluch; myši; Prostheses and Implants; Mice, Inbred C57BL; Animals; sluchové kmenové evokované potenciály; Mice; Reflex, Startle; Evoked Potentials, Auditory, Brain Stem; protézy a implantáty; úleková reakce; zvířata; Hearing